Characterization of nanocellulose obtained from Cereus Forbesii (a South American cactus) - Orrabalis, Camilo (2019)
Crystalline cellulose nanofibers are obtained from the bark of Cereus Forbesii, a cactus native to the arid areas of South America. The obtaining of cellulose nanofibers was carried out in several steps: pretreatment of the raw material, elimination of hemicellulose and lignin to obtain cellulose, and an acid hydrolysis of cellulose to obtain crystalline cellulose nanofibers. The cellulose nanofibers obtained have a crystallinity index of 82% and a nanofiber diameter of 18 nm. An average crystallite size of 6 nm was calculated for the crystalline domains that form cellulose nanofibers. The high crystallinity of the obtained cellulose nanofibers makes the sample very homogeneous and decomposes in a relatively narrow temperature range (between 290°C and 375°C). The complete degradation of crystalline cellulose polymer chains takes place between 375°C and 600°C. The morphological and structural studies are carried out by scanning electron microscopy of field emission, infrared spectrometry with Fourier transform, and powder X-ray diffraction. The thermal stability of the samples is determined by thermogravimetric analysis.